The Acceptability of Teachers’ Value Related Statements About Sustainable Development and Climate Change Among Non-Science and Science Major Students from Kosovo - Veselaj, Zeqir; Torkar, Gregor (European Journal of Sustainable Development, 2017)
In this paper we identify teachers’ value-laden statements about sustainable development and climate change that are (not) acceptable for pre-service students of preschool education (non-science majors) and student teachers of biology and chemistry (science majors) in their final year of university studies at the Faculty of Education University of Prishtina, Kosovo. Fifteen statements were provided and students had to choose among options “acceptable statement”, “unacceptable statement” and “cannot decide”. The questionnaire was completed by 63 students. The results show that the students expect their teachers to promote the principles of sustainable development. The majority of students considered as unacceptable any teacher’s statement that would throw doubt about the cause or necessity to act against climate change. Most of the students reported that they already heard unacceptable value-laden statements made by their teacher. Their most common reaction was to become alerted and discuss the statement with a colleague(s) in the classroom. Findings of the study do not provide clear conclusions on how science education of science and non-science major students influence on their acceptance of value-laden statements made by their teachers. Keywords: climate change, environmental education, science, statements, sustainable development, value-laden